Thermal Performance Investigation of Vapor Chamber Under Partial Heating and Different Heat Flux Conditions: Effects of Inclination Angle - Varol, Yasin; Öztop, Hakan Fehmi; Tamdogan, Enes; Parlak, Murat; Senocak, Safak Melih; Cosanay, Hakan (Asme, 2025)
The need for cooling technologies increases tremendously with raising demand on the powerful and compact electronics. There, it pushes the research and technology to the new investigations on varying heat transfer mechanisms and devices. While one of these devices is vapor chamber (VC), an experimental study has been carried out to investigate the heat transfer performance of a VC under partial heating, varying heat fluxes, and different inclination angles for different temperatures, in the current study. For this purpose, a VC with a dimension of 90 mm x 90 mm x 3 mm is evaluated via its resulting thermal resistance, performance, and the temperature distribution over the VC surface. There, the limited effect of inclination angle is observed on the performance, while the highest change is obtained with decreasing local heating surface area, thus increasing heat fluxes. Moreover, this trend is seen almost similar with a reasonable shift up or down according to the different temperature differences.
Keywords: vapor chamber; heat transfer; partial heating and cooling; thermal performance; inclination angle